Leucas Aspera - Medicinal Plant: A Review - R. SRINIVASAN,; B. RAVALI,; P. SUVARCHALA,; A. HONEY,; A. TEJASWINI,; P. NEERAJA, (International Journal of Pharma and Bio Sciences, 2011)
Leucas aspera commonly known as 'Thummichittu' is distributed throughout India and in the plains of Mauritius, java and philippines. The plant is used traditionally as an antipyretic and insecticide. Medicinally, it has been proven to possess various pharmacological activities like antifungal, antioxidant, antimicrobial, antinociceptive and cytotoxic activity and as an antidote to snake venom .Leucas leaves are used in chronic rheumatism. Further studies reveal the presence of various phytochemical constituents mainly triterpenoids, oleanolic acid, ursolic acid and b-sitosterol, nicotine, sterols, glucoside, diterpenes, phenolic compounds (4-(24-hydroxy-1-oxo-5-n-propyltetracosanyl)-phenol). These studies reveal that L. aspera is a source of medicinally active compounds and have various pharmacological effects; hence, this drug encourage finding its new therapeutic uses.